The Role of Women as Movers of Religious Moderation Through The Family - Anggraeni, Luciana; Sayyaf, R. Tanzil Fawaiq (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2022)
Amid the issue of Indonesian religious extremism, the role of women in strengthening literacy and religious moderation in the family is a serious concern. Preventing cases of radicalism can start from the closest point, namely the family. This is important to study because the role of women in the family is not only as mothers, but women can carry out their multi-role as individuals, wives, mothers, and community mobilizers in the implementation of religious moderation. Through parenting applied by mothers to children, they can integrate the values of justice and togetherness so children learn to respond to differences wisely. The role of mothers and women amid the Covid-19 pandemic is completing domestic work and indirectly acting as teachers for children. In this situation, mothers must be wise and need to supervise their children using technology, which is the main door for children to receive information. This study examines the role of women in the family as movers of religious moderation in Indonesia. The research method used is library research, which will focus on the literature, while the analysis used is descriptive-analytical. The result of this research is that women as mothers can instill values of religious moderation through child-rearing, women as wives can work together with their husbands in fostering a household ark that integrates the value of religious moderation in educating children as a mother, and the nuclear family. While women as a society have the potential to maintain and maintain inter-religious harmony, this potential is underutilized.